Systematic review of the impact of registration and screening on colorectal cancer incidence and mortality in familial adenomatous polyposis and Lynch syndrome. Issue 13 (December 2013) - Barrow, P.; Khan, M.; Lalloo, F.; Evans, D. G.; Hill, J.
<x xml:space="preserve">Abstract</x> Background The British Society of Gastroenterology recommends that all familial adenomatous polyposis (FAP) and Lynch syndrome (LS) families are screened in the context of a registry. This systematic review was performed to appraise the published evidence for registration and screening in relation to colorectal cancer (CRC) incidence and mortality. Methods Five electronic databases were searched using a combination of medical subject heading terms and free‐text keywords. Titles and abstracts were scrutinized by two independent reviewers. Inclusion criteria were English‐language studies describing CRC incidence and/or mortality in patients with FAP or LS, with comparison of either: screened and unscreened patients, or time periods before and after establishment of the registry. Results Of 4668 abstracts identified, 185 full‐text articles were selected; 43 studies fulfilled the inclusion criteria. No randomized clinical trial evidence was identified. For FAP, 33 of 33 studies described a significant reduction of CRC incidence and mortality with registration and screening. For LS, nine of ten studies described a reduction of CRC incidence and mortality with registration and screening. Five studies (FAP, 2; LS, 3) provided evidence for complete prevention of CRC‐related deaths during surveillance. Clinical and statistical heterogeneity prevented pooling of data for meta‐analysis. Conclusion Studies consistently report that registration and screening result in a reduction of CRC incidence and mortality in patients with FAP and LS (level 2a evidence, grade B recommendation). Funding and managerial support for hereditary CRC registries should be made available. Presented to the Association of Surgeons of Great Britain and Ireland 2013 Congress, Glasgow, UK, May 2013, and to the Annual Meeting of the Association of Coloproctology of Great Britain and Ireland, Liverpool, UK, July 2013; published in abstract form as Br J Surg 2013; 100(Suppl 7): 123–124 and as Colorectal Dis 2013; 15(Suppl 1): 4